1998
DOI: 10.1002/(sici)1520-6327(1998)37:1<33::aid-arch5>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphosis of the red flour beetle,Tribolium freemani Hinton (Coleoptera: Tenebrionidae): Alteration of octopamine content modulates activity of juvenile-hormone esterase, ecdysteroid level, and pupation

Abstract: Under crowded conditions, Tribolium freemani larvae exhibited a delay in the increase of octopamine (OA) content, activity of juvenile‐hormone esterase (JHE), and ecdysteroid content, leading to a delay in pupation compared to the larvae under isolated conditions. Under crowded conditions, a peak OA content appeared at days 2–4, followed by a peak of JHE activity at day 7, the second OA peak at day 9, and an ecdysteroid peak at day 11 of the instar. Optical stress, on the other hand, caused an increase in OA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Novaluron action is by chitin inhibition according to Soltani et al (1995), Mulla et al (1974Mulla et al ( , 2003 and Kostyukovsky and Trostanetsky (2004) for novaluron and MOSO action as growth regulator and by blocking the respiratory surfaces. According to Hirashima et al 1998, Enan, 2001) some plant essential oil block the octopamine neuroreceptors that regulate the movement, heart rate, behaviour, metabolism, and pupation of insects. This regulatory activity of these two insecticides was evidenced by the death recorded in both 1 st and 4th instar larvae and inhibition of their emergence to pupae.…”
Section: Discussionmentioning
confidence: 99%
“…Novaluron action is by chitin inhibition according to Soltani et al (1995), Mulla et al (1974Mulla et al ( , 2003 and Kostyukovsky and Trostanetsky (2004) for novaluron and MOSO action as growth regulator and by blocking the respiratory surfaces. According to Hirashima et al 1998, Enan, 2001) some plant essential oil block the octopamine neuroreceptors that regulate the movement, heart rate, behaviour, metabolism, and pupation of insects. This regulatory activity of these two insecticides was evidenced by the death recorded in both 1 st and 4th instar larvae and inhibition of their emergence to pupae.…”
Section: Discussionmentioning
confidence: 99%
“…Such a stress effect could be mediated by JH, as this hormone is known to be sensitive to stress in a variety of insect species (Jankovic-Hladni, 1991). Other neuroendocrine factors could be involved, such as the biogenic amine octopamine (Hirashima, Takeya, Taniguchi, and Eto, 1995;Hirashima, Hirokado, Tojikubo, Takeya, Taniguchi, and Eto, 1998). Grabbing a bee with forceps and holding its legs in an alligator clamp for several minutes triggers a transient increase in octopamine levels in the bee brain (Harris and Woodring, 1992), and high brain octopamine levels are associated with foraging (Harris and Woodring, 1992;Wagener-Hulme, Kuehn, Schulz, and Robinson, 1999;Schulz and Robinson, 1999).…”
Section: Figmentioning
confidence: 99%
“…In locusts, OA plays an important role in flight activity [ 7 ] and olfactory attraction [ 8 ]. In Tribolium freemani, OA was reported to modulate the activity of the juvenile hormone esterase [ 9 ]. It has been previously suggested that OA could modulate various behaviors in the model insect Drosophila melanogaster [ 1 ].…”
Section: Introductionmentioning
confidence: 99%